2022
DOI: 10.3390/chemosensors10090371
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Viscosity and Salt Interference for Planar Iridium Oxide and Silver Chloride pH Sensing Electrodes on Flexible Substrate

Abstract: The equivalency of pH measurements between aqueous and non-aqueous or viscous solutions is of great interest in biomedical applications as well for processing food and pharmaceuticals. Commercial glass-type electrodes have practical limitations, such as bulky sizes and membrane clogging in viscous environments. In this study, planar and flexible electrochemical pH sensors with iridium oxide as the sensing film have been developed by sol-gel and oxidation processes. A reference electrode was prepared by screen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…In this study, we attempted to measure the pH of the product and not homogenate, thus, setting a challenging task. The challenges of measuring the pH in viscous samples correlate well with the findings of Chawang et al, where authors have demonstrated that the viscosity of starch significantly influenced the measured potential of the iridium oxide electrode.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…In this study, we attempted to measure the pH of the product and not homogenate, thus, setting a challenging task. The challenges of measuring the pH in viscous samples correlate well with the findings of Chawang et al, where authors have demonstrated that the viscosity of starch significantly influenced the measured potential of the iridium oxide electrode.…”
Section: Resultssupporting
confidence: 78%
“… 30 Furthermore, the viscosity of the samples can negatively affect the potential of a metal oxide electrode. 33 A more detailed study of this phenomenon is necessary and will be addressed in our future work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 These response times depend on factors such as electrode design, manufacturer, sample conditions, and are influenced by temperature, ionic strength, viscosity, and the presence of interfering chemical species (refer to Table S1 in the ESI † for the response times of some commercially available sensors). [17][18][19][20][21] Recent work by our research group addressed these problems by modifying amperometric microsensors with an acidic conversion chamber to measure the total pool pH-dependent analytes. This principle allowed for in situ conversion of the total pool to a single measurable species close to the sensing unit.…”
Section: Introductionmentioning
confidence: 99%
“…Other characterizations such as hysteresis, drift, fluctuation, and deviation test were performed to evaluate the stability as well as the repeatability of IrOx-based pH sensor. Further, the fabricated electrodes presented a suitable data from pH 4 to 9 when tested against a synthetic sweat [124]. Similarly, PEDOT:PSS and IrOx NMs provided the pH sensing matrix due to the redox chemistry of IrOx-complex as it exhibited Ir-III/Ir-IV redox couple, which ultimately triggered PEDOT:PSS chain that extracted electrons from the polymeric (PEDOT:PSS) film, causing to current flow across the film (Figure 13 (B)).…”
mentioning
confidence: 96%